1977
DOI: 10.1530/jrf.0.0500281
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative examination of the proteins of rat uterine luminal fluid during pro-oestrus and pregnancy and comparison with those of serum

Abstract: Rat serum and uterine luminal proteins at two distinct endocrinological stages were analyzed electrophoretically. The quantitative relationships between the major macromolecular fractions were calculated from the densitometer scans. At pro-oestrus there was a marked increase in the total luminal proteins which was probably not due to transudation of serum into the lumen because of the presence of large amounts of two proteins, of approximate mol. wt 125,000 and 130,000, which were not detected in serum. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…Previous studies have indicated that the protein content of uterine luminal fluid is considerably higher at pro-oestrus than during pregnancy (Surani, 1977a) and this has been confirmed by the present results. The differences in protein content of uterine luminal fluid after ovariectomy and during pro-oestrus and pregnancy (Day 5) were probably due to differences in endocrine status, namely high oestrogen levels during pro-oestrus as against high levels of progesterone and medium levels of oestradiol during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have indicated that the protein content of uterine luminal fluid is considerably higher at pro-oestrus than during pregnancy (Surani, 1977a) and this has been confirmed by the present results. The differences in protein content of uterine luminal fluid after ovariectomy and during pro-oestrus and pregnancy (Day 5) were probably due to differences in endocrine status, namely high oestrogen levels during pro-oestrus as against high levels of progesterone and medium levels of oestradiol during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Samples of such proteins are usually obtained by flushing the lumen (Surani, 1975(Surani, , 1977 Gore-Langton & Surani, 1976;Pratt, 1977;Aitken, 1977). I had been puzzled by the large amounts of material so obtained from mouse uteri on Days 4-5 of pregnancy, because at this time the lumen virtually disappears, the luminal epithelial surfaces coming into such close proximity that the microvilli of the opposing surfaces interdigitate or disappear (Mayer, Nilsson & Reinius, 1967;.…”
Section: Introductionmentioning
confidence: 99%
“…Oestrogens appear to be principal regulators o f IgA plasma cells to the uterus and upon uterine levels o f secretory component (Sullivan & Wira, 1981). Thus, the transfer o f IgA and IgG across the uterine epithelium in response to oestrogen occurs by two distinct mechanisms, one o f which (IgA) is specific and likely to require protein synthesis (Wira et ul., 1984) and the other (IgG) (Hall et al, 1977;Surani, 1977)…”
Section: Permeability and Transport Properties Of Uterine Epitheliummentioning
confidence: 99%
“…material which does not adsorb initially to the plasma membrane) (Morales & Hermo, 1983). Thus, endocytosis of this type has been suggested to participate in the reabsorption of uterine fluid from the lumen (Enders & Nelson, 1973;Parr & Parr, 1974, 1977. However, because mannose-specific binding sites for horseradish peroxidase have been described for various cells in the rat (Straus, 1983;Wilson & King, 1986), internalization of this protein might be more specific than previously considered.…”
Section: Uptake and Release By Endometrial And Embryonic Cellsmentioning
confidence: 99%